Childhood BMI trajectories and sociodemographic factors in an Italian pediatric population - Erich Batzella; Joaquin Gutierrez de Rubalcava Doblas; Gloria Porcu; Silvia Bressan; Elisa Barbieri; Carlo Giaquinto; Anna Cantarutti; Cristina Canova (Scientific Reports)
Abstract Childhood obesity is a growing global concern due to its long-term health consequences. Yet, more research relying on multiple time-point BMI measurements is warranted to gain further insight into obesity’s temporal trends. We aimed to identify BMI trajectories in children aged 2–10 years and evaluate their association with sociodemographic factors. This retrospective cohort study utilized data from the PEDIANET registry, containing sociodemographic, clinical, and prescribing information on patients assisted by Italian family pediatricians, linked to the corresponding area deprivation index. 29,576 children with at least 10 years of follow-up, born at term with normal birthweight, and at least three plausible BMI measurements were identified. BMI z-score trajectories were calculated using Group-Based Trajectory Modeling, and mixed multinomial logistic regression was used to assess their association with the sociodemographic factors. A secondary analysis examined BMI trajectories from ages 2–7 years (n = 58,509). Four BMI z-scores trajectories, all with quadratic shape, were identified as the optimal fit: “stable-low-weight” (27.5%), “normal-weight” (40.9%), “stable-moderate-increase” (24.2%), and “overweight-to-obese” (7.5%). Females, children residing in Southern and Island regions, and those from more deprived socioeconomic areas had a higher probability of following the “overweight-to-obese” group compared to the “normal-weight” trajectory. Sex and area of residence had similar effects on the “stable-moderate-increase” trajectory. Conversely, females and children residing in Central Italy were less likely to belong to the “stable-low-weight trajectory”. This study highlighted a considerable heterogeneity in BMI trajectories in pediatric age, emphasizing the effect of sociodemographic inequalities on growth patterns with models capable of capturing the dynamic nature of the phenomenon.